2014
DOI: 10.1021/bm5010977
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Glycopolymeric Decorated Gold Nanoparticles Functionalized with Gold-Triphenyl Phosphine as Anti-Cancer Agents

Abstract: In this study, statistical glyco-dithiocarbamate (DTC) copolymers were synthesized by reversible addition-fragmentation chain transfer polymerization (RAFT) and subsequently used to prepare glyconanoparticles and conjugated glyconanoparticles with the anticancer drug, gold(I) triphenylphosphine. These glyconanoparticles and the corresponding conjugates were then tested for their in vitro cytotoxicity in both normal and cancer cell lines using Neutral Red assay. The glyconanoparticles and their Au(I)PPh3 conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 67 publications
0
37
0
Order By: Relevance
“…Recently, it has been reported the interesting synthesis of AuNPs coated with glyco-polymers and functionalized with gold(I) triphenylphosphine (Fig. 7) [88]. This work showed the potentiality of these structures as novel cancer therapeutic drugs.…”
Section: Reviewmentioning
confidence: 75%
“…Recently, it has been reported the interesting synthesis of AuNPs coated with glyco-polymers and functionalized with gold(I) triphenylphosphine (Fig. 7) [88]. This work showed the potentiality of these structures as novel cancer therapeutic drugs.…”
Section: Reviewmentioning
confidence: 75%
“…Reproduced with permission from [55]. Reproduced with permission from [59]. Others have shown that lactose modified super paramagnetic iron oxide nanoparticles and gold nanoparticles significantly accumulate in mice liver and were used as source of computed tomography [57,58].…”
Section: Pullulan-based Nanoparticlesmentioning
confidence: 99%
“…The amine content of cationic glycopolymers was modified with dithiocarbamate motif, in a postpolymerization modification approach. Dithiocarbamate and gold triphosphine Au(PPh 3 )Cl-functionalized gold nanoparticles were then prepared by UV reduction of gold salt, as shown in Figure 19 [59].…”
Section: Pullulan-based Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…4954 Enhanced fluorescence, which stems from the GSH-mediated cleavage of NA-S-BA, was observed in ASGPR-expressing HepG2 cells as compared to ASGPR-deficient cancer cells (HeLa cells) and ASGPR-deficient non-tumorigenic cells (NIH3T3 cells). 55,56 Accordingly, nanoparticles conjugated with CPT-S-BA exhibit distinct selectivity for cancer cells over normal cells, without compromising the chemotherapeutic efficacy of the native CPT. A noteworthy advantage is that by simply changing the carbohydrate moiety on the GNP, this system possesses the potential to target a variety of cancer cells based on the lectins expressed on the cell surface and the corresponding conjugated carbohydrates.…”
Section: Introductionmentioning
confidence: 99%